Fingerprints of magma mingling processes within the Miocene Zebin tuff cone feeding system (Jicin Volcanic Field, Czech Republic) - Rapprich,V.; Shields,S.; Halodova,P.; Lindline,J.; van Wyk de Vries,B.; Petronis,M.S.; Valenta,J. (Journal of Geosciences, 2017)
A well-preserved set of partly eroded mid-Miocene scoria cones and tuff cones are exposed in the Jicin Volcanic Field, Czech Republic. Zebin Hill, a formerly quarried tuff cone with an exposed conduit and associated dikes, offers an opportunity to study magmatic processes within the high-level feeding system of a small monogenetic volcano. Two types of dikes and associated “blob-like” intrusions were observed. Pure basanite dikes predominate in the center of the cone, whereas its peripheries were intruded by mingled dikes. The mingled dikes consist of mm-scale basanitic domains enclosed in a network of trachyandesitic dikelets. Locally, hybrid domains with intermediate characteristics were observed. The basanite dikes and basanite enclaves within mingled dikes contain normally-zoned minerals (Fo90 to Fo70 olivine, Mg-rich to Mg-poor diopside, labradorite to andesine composition of plagioclase) indicative of basanite magma evolution during ascent. In contrast, the trachyandesite and hybrid enclaves in mingled dikes show reverse zoning of minerals (Mg-poor to Mg-rich diopside, sanidine to oligoclase feldspar composition) indicative of magma hybridization.This study suggests that the Zebin Volcano did not develop from a simple monogenetic system and through a simple central axis feeder; rather, Zebin Hill evolved from a complex magma feeding/storage system and through a complex feeder network. We conclude that the simple external structure of a monogenetic volcano may sometimes hide rather complex magmatic plumbing systems encompassing compositionally contrasting rocks/magmas.
Keywords: magma mingling; basanite; trachyandesite; mineral chemistry; Zebin tuff cone; Jicin Volcanic Field